2022
DOI: 10.1007/s12519-022-00637-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and mortality risk prediction model in children with acute myocarditis

Abstract: Background Acute myocarditis (AMC) can cause poor outcomes or even death in children. We aimed to identify AMC risk factors and create a mortality prediction model for AMC in children at hospital admission. Methods This was a single-center retrospective cohort study of AMC children hospitalized between January 2016 and January 2020. The demographics, clinical examinations, types of AMC, and laboratory results were collected at hospital admission. In-hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…In our center, we found that AFM was more prevalent in females than in males among children, which is inconsistent with the results of two previous studies [23,24], but in alignment with the results reported by Shanghai Children's Medical Center [25]. Pediatric AFM can be non-speci c, commonly symptomized by vomiting, fever, abdominal pain, and chest tightness.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our center, we found that AFM was more prevalent in females than in males among children, which is inconsistent with the results of two previous studies [23,24], but in alignment with the results reported by Shanghai Children's Medical Center [25]. Pediatric AFM can be non-speci c, commonly symptomized by vomiting, fever, abdominal pain, and chest tightness.…”
Section: Discussioncontrasting
confidence: 99%
“…Some children also present with syncope, poor appetite, coughing, dizziness, shortness of breath, headache, edema, pallor, discomfort in the precordial area, coma, drowsiness, sudden respiratory and cardiac arrest, diarrhea, etc. Besides, AFM may simultaneously involve multiple systems, like the digestive, nervous, and respiratory systems [24].…”
Section: Discussionmentioning
confidence: 99%
“…To identify reliable predictors and address collinearity among independent variables, we will employ the LASSO regression analysis 24. As the outcome event pertains to myocarditis development in children, we will use multiple logistic regression analyses18 25–29 to construct an early prediction model for myocarditis. This model estimates the probability of myocarditis by assessing the child’s condition during a visit.…”
Section: Discussionmentioning
confidence: 99%